Initiation of Infectious Disease Clinical Pharmacist’s Role in an Antimicrobial Stewardship Program - An Experience from Saudi Arabia - Abuelsoud, Nermeen N. (Asian Journal of Pharmaceutics (AJP), 2019)
Background: Pharmacists are leading antimicrobial stewardship all over the world. In the Middle Eastern hospitals, the concepts of infectious disease clinical pharmacists and antimicrobial stewardship programs are not yet implemented. Aim: The aim of this study is to set a base for antimicrobial use in a tertiary care hospital in Saudi Arabia through determination of the patterns of antimicrobial resistance and sensitivity and to use these data as a base to initiate the clinical pharmacist’s role in an antimicrobial stewardship program. Methods: A total of 1487 cultures and sensitivity reports were collected from all departments of the hospital during a 1-year period, reports were analyzed to detect the percentages of different microorganisms, their resistance/sensitivity patterns and to outline recommendations about antimicrobial use within the hospital. The roles of infectious disease pharmacist in an antimicrobial stewardship program were initiated through three phases. Results: Approximately 30% of the detected microorganisms were Gram-positive. Staphylococcus accounted for 84% of the Grampositive bacteria. The remaining bacteria (70%) were Gram-negative, consisting of Pseudomonous aeruginosa (27%), Klebsiella (19%), Acinetobacter (17%), and Escherichia coli (15%). 81% of the Gram-negative organisms were sensitive to piperacillin/tazobactam, 76% to imipenem/cilastatin, 73% to amikacin, 62% to gentamycin, 54% to ciprofloxacin, and 51% to cephalosporins. Sensitivity to linezolid and vancomycin was approximately 99% among Gram-positive organisms. Conclusions: To minimize the emergence of microbial resistance, infectious disease pharmacists should assist physicians in optimizing antimicrobials use. Implementation of an antimicrobial stewardship program in this hospital had a great impact in terms of optimizing antimicrobials use.